From problematic soil to engineered fill: Transforming granite residual soil with clay improvement - Fang Dang; Hong Guo; Ya Wang; Wenyang Li; Hong Jiang; Jiangtao Fu (PLoS ONE, 2026)
To investigate the enhancement effect of clay on the mechanical properties of granite residual soil in the Qinba Mountains of China, this study systematically examined the influence of clay content on the liquid and plasticity index, compaction behavior, compressibility, cohesion and internal friction angle of the soil. The analysis used a range of laboratory tests. These include tests to measure liquid and plastic limit determinations. The analysis also used tests for compaction and compression and tests that examine direct shear. Observations of structures at small scale provided additional data. The findings show that particles of clay fill spaces in soil. This filling increases how compact the soil is. The filling also improves capacity to hold water. Hydroxyl groups that the clay introduces allow this improvement. The adsorption of water molecules by the clay also supports this effect. When the clay content increases, the plasticity index shows increase and the maximum moisture content shows increase in the granite residual soil. The clay content that reaches 30% produces the maximum dry density that shows the peak value in the soil, and this represents increase of approximately 21.4% when results compare to the soil without improvement. The compression coefficient decreases to the minimum level at the same clay content, and this reflects reduction of 75%. The cohesion of the soil mass shows increase that relates to increasing clay content in a linear pattern. The internal friction angle shows gradual decrease with the clay content increase, and this angle tends to stabilize when the clay content exceeds 30%. These findings indicate that clay provides effective improvement material for the engineering properties that the granite residual soil contains. The approach that uses clay offers reliable reference for applications that involve roadbed filling.